PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DIVISI DIE CASTING PADA PT. CABININDO PUTRA - Farhan Adna Yaffi; Tubagus Akbar Ikhwandi; Agung Surya Dwianto (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
This research is to prove that PT Carbinindo can maintain employee discipline well, with the average educational background of its employees being vocational school graduates, and to prove the work environment, namely from the results of the questionnaire answers obtained, such as lighting, air circulation, and no unpleasant odors in the place. work, there is no environmental noise between employees and so on. This research aims to find out whether work discipline has a positive effect on employee performance and whether the work environment has a positive effect on employee performance. Data was obtained by distributing questionnaires directly to 30 employee respondents in the Die Casting Division of PT Cabinindo Putra. This research is descriptive quantitative research. The results of the analysis in this research used Validity Test, Reliability Test, Multiple Linear Regression Analysis, Hypothesis Testing using the t Test (partial) and Determination Coefficient Test (R2), using SPSS version 25 software. The research results show that 1) Work discipline has an effect significantly positive effect on employee performance, 2) The work environment has a negative effect on employee performance at PT Cabinindo Putra.